2023
DOI: 10.1111/epi.17531
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and predictors of health‐related quality of life in Dravet syndrome: A 10‐year, prospective follow‐up study

Abstract: Objective Dravet syndrome (DS) is a severe developmental and epileptic encephalopathy, leading to reduced health‐related quality of life (HRQOL). Prospective outcome data on HRQOL are sparse, and this study investigated long‐term predictors of HRQOL in DS. Methods One hundred thirteen families of SCN1A‐positive patients with DS, who were recruited as part of our 2010 study were contacted at 10‐year follow‐up, of which 68 (60%) responded. The mortality was 5.8%. Detailed clinical and demographic information was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…One hundred thirteen individuals who exhibited a DS phenotype and who had a positive SCN1A mutation were posted questionnaires, of whom 68 (60%) responded. 21 The median age was seven years at baseline assessment (6 months to 42 years old, IQR = 4–15) and 17 (10 to 39 years old, IQR = 14–24) at follow-up. Sixty-two out of 141 (44%) were male in the initial study, compared to 36 out of 68 (53%) at follow-up ( P = 0.7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred thirteen individuals who exhibited a DS phenotype and who had a positive SCN1A mutation were posted questionnaires, of whom 68 (60%) responded. 21 The median age was seven years at baseline assessment (6 months to 42 years old, IQR = 4–15) and 17 (10 to 39 years old, IQR = 14–24) at follow-up. Sixty-two out of 141 (44%) were male in the initial study, compared to 36 out of 68 (53%) at follow-up ( P = 0.7).…”
Section: Resultsmentioning
confidence: 99%
“…The majority were attributed to Sudden Unexpected Death in Epilepsy (SUDEP, 4/7) and the remaining three cases were due to status epilepticus, acute respiratory distress syndrome and one unknown cause. 21 When asked whether SUDEP had been discussed with a medical professional, 24 of 68 carers (35%) indicated that this was not the case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SUDEP-related deaths represent 53%-61% of the reported deaths compared with 14.5% in patients with new-onset epilepsy. 11,17 A multi-institutional study involving 91 hospitals reported a mortality rate of 10.1%. 18 Critical incidents were reported by the caregiver in a high proportion of patients, and cardiac or respiratory arrest with the need for resuscitation was reported in more than 20% of patients, of which 72.7% were associated with a seizure (0-60 min postictal).…”
Section: Discussionmentioning
confidence: 99%
“…Annual mortality rates exceeding 5% are reported in patients with DS, which is much higher than in other types of epilepsy. SUDEP‐related deaths represent 53%–61% of the reported deaths compared with 14.5% in patients with new‐onset epilepsy 11,17 . A multi‐institutional study involving 91 hospitals reported a mortality rate of 10.1% 18 .…”
Section: Discussionmentioning
confidence: 99%